KAJIAN EKONOMI PEMANFAATAN PLTS ATAP DI GEDUNG RUMAH JABATAN GUBERNUR PROVINSI BALI - Diva Aristia, Gusti Bagus; Dwi Giriantari, Ida Ayu; Sukerayasa, I Wayan (Jurnal SPEKTRUM, 2023)
To meet the high demand for electrical energy, an alternative solution that can be applied is the use of New and Renewable EnergyIndonesia targets to achieve Net Zero Emissions (NZE) by 2060. Planning for a rooftop PLTS at the Office of the Governor of the Province of Bali is expected to be able to assist in the expansion of PLTS in the Province of Bali in terms of strengthening Governor Regulations/Regional Regulations that support the use of Solar Power Plants. The design of the rooftop PLTS at the Bali Province Governor's Office Building was carried out using 4 scenarios. Scenario 1 is a design that utilizes the roof area facing the north side. Scenario 2 is by utilizing the roof area only to meet the peak load of the building. Scenario 3 is a design that utilizes the entire roof area of the building that best meets the criteria. Meanwhile, scenario 4 is scenario 2 but uses a microinverter device. The Scenario 2 PLTS design is studied economically because the return on investment is the fastest compared to the other scenario PLTS designs. Based on the economic feasibility analysis of the investment, scenario 2 design has a Net Present Value (NPV) of Rp. 158,771,001, Profitability Index (PI) of 1.32 and a Discounted Payback Period (DPP) of 10.7 years.